Statistical principles for the design of experiments - Mead, R. [ (Roger)]; Gilmour, S. G.; Mead, A. [ (Andrew)] (Cambridge series in statistical and probabilistic mathematics, 2012)
"This book is about the statistical principles behind the design of effective experiments and focuses on the practical needs of applied statisticians and experimenters engaged in design, implementation and analysis. Emphasising the logical principles of statistical design, rather than mathematical calculation, the authors demonstrate how all available information can be used to extract the clearest answers to many questions. The principles are illustrated with a wide range of examples drawn from real experiments in medicine, industry, agriculture and many experimental disciplines. Numerous exercises are given to help the reader practise techniques and to appreciate the difference that good design can make to an experimental research project" -- Provided by publisher